Pressure‐Dependent Mechanical and Thermal Properties of Lead‐Free Halide Double Perovskite Cs2AgB″X6 (B″═In, Bi; X═Cl, Br, I). Issue 12 (14th October 2019) - Su, Jie; Zhang, Zhao; Hou, Jie; Liu, Mengyu; Lin, Zhenhua; Hu, Zhaosheng; Chang, Jingjing; Hao, Yue
Abstract: Lead‐free halide double perovskites Cs2 AgB″X6 (B″═In, Bi; X═Cl, Br, I) are emerging as excellent photoelectric materials. Investigating their mechanical and thermodynamic properties under hydrostatic pressure is vital for designing high‐performance photoelectric devices. Although Cs2 AgB″X6 exhibits similar cubic structures, the bond length and strength characteristics of Cs2 AgInX6 are different to those of Cs2 AgBiX6, and Cs2 AgB″X6 exhibits obvious mechanical anisotropic. Upon experiencing pressure, the stablility of Cs2 AgB″X6 is improved and without phase transition, and its bond characteristics are unified, which is different to lead halide perovskites. Compared to Cs2 AgBiX6, Cs2 AgInX6 may be more suitable to flexible devices due to its higher shear and bulk modulus. In addition, the thermal conductivities of Cs2 AgBiX6 (X═Cl, Br) and Cs2 AgBiX6 (X═Cl, Br, I) are 0.41, 0.32, 0.37, 0.29, 0.23 W m −1  K −1, and can be enlarged by pressure and surpass that of lead halide perovskite. Moreover, all the Cs2 AgB″X6 (B″═In, Bi; X═Cl, Br, I) possess the same saturated heat capacity of about 249.3 J mol −1  K −1 . These variations of mechanical and thermal properties are elucidated by the bonds. These results maybe also applicable to other double perovskites, and beneficial for designing devices with better optoelectronic performance. Abstract : Although Cs2 AgB″X6 exhibits similar cubic structures, Cs2 AgInX6 is more suitable for use in flexible devices due to its higher shear and bulk moduli. Cs2 AgInCl6 exhibits a large thermal conductivity of about 0.41 W m −1  K −1, which can be increased by pressure to surpass that of lead halide perovskite. Pressure can unify the bond characters of Cs2 AgB″X6 and improve its stability without phase transition.